Pre-clinical toxicity assessment of Artemisia absinthium extract-loaded polymeric nanoparticles associated with their oral administration - Sana Kauser; Mohd Mughees; Sanskriti Swami; Saima Wajid (Frontiers Media S.A., 2023)
Background: This study was designed to quantify the composition of the ethanolic extract of Artemisia absinthium through gas chromatography-mass spectrometry analysis and ensure in vivo safety of A. absinthium extract-loaded polymeric nanoparticles (ANPs) before considering their application as a drug carrier via the oral route.Methods: We synthesized N-isopropylacrylamide, N-vinyl pyrrolidone, and acrylic acid crosslinked polymeric NPs by free-radical polymerization reaction and characterized them by Fourier-transform infrared spectroscopy, transmission electron microscopy, and dynamic light scattering spectroscopy. Different concentrations of extract (50 mg/kg, 300 mg/kg, and 2,000 mg/kg body weight) were encapsulated into the hydrophobic core of polymeric micelles for the assessment of acute oral toxicity and their LD50 cut-off value as per the test procedure of OECD guideline 423. Orally administered female Wistar rats were observed for general appearance, behavioral changes, and mortality for the first 30 min, 4 h, 24 h, and then, daily once for 14 days.Result: ANPs at the dose of 300 mg/kg body weight were used as an initial dose, and rats showed few short-lived signs of toxicity, with few histological alterations in the kidney and intestine. Based on these observations, the next set of rats were treated at a lower dose of 50 mg/kg and a higher dose of 2,000 mg/kg ANPs. Rats administered with 50 mg/kg ANPs remained normal throughout the study with insignificant histological disintegration; however, rats treated at 2,000 mg/kg ANPs showed some signs of toxicity followed by mortality among all three rats within 24-36 h, affecting the intestine, liver, and kidney. There were no significant differences in hematological and biochemical parameters among rats treated at 50 mg/kg and 300 mg/kg ANPs.Conclusion: We conclude that the LD50 cut-off value of these ANPs will be 500 mg/kg extract loaded in polymeric NPs.